Febrile temperature causes transcriptional downregulation of Plasmodium falciparum Sirtuins through Hsp90‐dependent epigenetic modification. Issue 5 (13th February 2021) - Tabassum, Wahida; Bhattacharyya, Sunanda; Varunan, Shalu M.; Bhattacharyya, Mrinal Kanti
Abstract: Sirtuins ( PfSIR2A and PfSIR2B ) are implicated to play pivotal roles in the silencing of sub‐telomeric genes and the maintenance of telomere length in P. falciparum 3D7 strain. Here, we identify the key factors that regulate the cellular abundance and activity of these two histone deacetylases. Our results demonstrate that PfSIR2A and PfSIR2B are transcriptionally downregulated at the mid‐ring stage in response to febrile temperature. We found that the molecular chaperone PfHsp90 acts as a repressor of PfSIR2A & B transcription. By virtue of its presence in the PfSIR2A & B promoter proximal regions PfHsp90 helps recruiting H3K9me3, conferring heterochromatic state, and thereby leading to the downregulation of PfSIR2A & B transcription. Such transcriptional downregulation can be reversed by the addition of 17‐(allylamino)‐17‐demethoxygeldanamycin or Radicicol, two potent inhibitors of PfHsp90. The reduced occupancy of PfSir2 at sub‐telomeric var promoters leads to the de‐repression of var genes. Thus, here we uncover how exposure to febrile temperature, a hallmark of malaria, enables the parasites to manipulate the expression of the two prominent epigenetic modifiers PfSir2A and PfSir2B. Abstract : Eukaryotic organisms sense changes in the environment and accordingly amend gene expression through epigenetic modifications. The malaria parasites are exposed to various temperature shifts during their complex life cycle. Here we uncover how an exposure to febrile temperature modulates the expression of two epigenetic erasers, namely PfSir2A and PfSir2B leading to the dysregulation of the virulence genes that could impact the chronicity of malaria infection. We found that these two master epigenetic regulator in Plasmodium are themselves regulated transcriptionally by epigenetic modification. Here we show that Hsp90, a molecular chaperone, is the key link between environmental heat stress and chromatin modification in this parasite. Additionally, understanding the molecular mechanism underlying PfSIR2 gene regulation might offer novel intervention strategies for curbing malaria.